Understanding the challenges Muslim women face in adventure tourism - Md Nasir, Maheran; Md Sawari, Siti Salwa; Alam, Azhar (IIUM Press, 2025)
This study explores the challenges faced by Muslim women in adventure tourism, aiming to uncover social, cultural, and logistical barriers that limit their participation. Using a phenomenological qualitative approach, semi-structured interviews were conducted with nine Muslim women who actively engage in adventure activities. The findings reveal that participants face several obstacles, including family related safety concerns, discrimination, harassment, and a lack of appropriate infrastructure and privacy. Despite these challenges, the women expressed a strong desire to continue participating in such activities, highlighting the need for tourism providers to adopt gender-sensitive and culturally respectful practices. While the study is limited by its small sample size and specific cultural context, it offers important insights for future research and industry practices. Practical implications include the development of inclusive services such as female only groups, private facilities, and culturally aware staff training. This research adds original value by shedding light on an underrepresented group in tourism literature and offers actionable recommendations to enhance the travel experiences of Muslim women.